2016
DOI: 10.1242/jcs.189944
|View full text |Cite
|
Sign up to set email alerts
|

HMGB2 regulates satellite-cell-mediated skeletal muscle regeneration through IGF2BP2

Abstract: Although the mechanism underlying modulation of transcription factors in myogenesis has been well elucidated, the function of the transcription cofactors involved in this process remains poorly understood. Here, we identified HMGB2 as an essential nuclear transcriptional co-regulator in myogenesis. HMGB2 was highly expressed in undifferentiated myoblasts and regenerating muscle. Knockdown of HMGB2 inhibited myoblast proliferation and stimulated its differentiation. HMGB2 depletion downregulated Myf5 and cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…The short isoform of IGF2BP2, p62, is overexpressed in HCC with stem-like features and hypervascularization, and the livers of p62 transgenic mice highly express the stem cell marker DLK1 and generate tumors with more aggressive and stem-like phenotype [ 27 ]. Consistent with these observations in CSCs are the determinant roles of IGF2BP2 in the differentiation of NPCs [ 16 ] and myoblasts [ 131 , 132 ].…”
Section: Igf2bp2 and Cancer Stem Cellssupporting
confidence: 54%
“…The short isoform of IGF2BP2, p62, is overexpressed in HCC with stem-like features and hypervascularization, and the livers of p62 transgenic mice highly express the stem cell marker DLK1 and generate tumors with more aggressive and stem-like phenotype [ 27 ]. Consistent with these observations in CSCs are the determinant roles of IGF2BP2 in the differentiation of NPCs [ 16 ] and myoblasts [ 131 , 132 ].…”
Section: Igf2bp2 and Cancer Stem Cellssupporting
confidence: 54%
“…However, in articular cartilage, loss of HMGB2 reduces the regeneration capacity of mesenchymal stem cells by increasing apoptosis (42). Similarly, knockdown of HMGB2 decreased the number of muscle stem (satellite) cells by inhibiting proliferation and stimulating differentiation, thereby leading to the impaired muscle regeneration (43). Our study showed that the functional effects of HMGB2 on HSCs and blood system are similar to those in mesenchymal and muscle stem cells.…”
Section: Discussionsupporting
confidence: 56%
“…In support of this, HMGB2 was reported to promote the proliferation of satellite cells, which are quiescent stem cells in the muscle, orchestrating muscle regeneration (Zhou et al, ). In that report, Insulin‐like growth factor‐2 mRNA‐binding protein (IGF2BP2), a member of the family of IGF2 mRNA‐binding proteins known to bind to various RNAs such as IGF2 for enhancement of its translation, was shown to be a downstream target of HMGB2 and to increase the production of proteins encoded by cell cycle‐related genes to evoke the activation of quiescent satellite cells.…”
Section: Discussionmentioning
confidence: 91%